EMPIRICAL JURIDICAL REVIEW OF EARLY MARRIAGE DISPENSATION (Case Study of the Cikarang and Pangkal Pinang Religious Courts) - Meliza, Meliza; Hardianto, Hanif; Gumbira, Seno Wibowo; apriandhini, Megafury; Chairunnisa, Madina Dzakkiyyah; Isfarin, Nadia Nurani (Faculty of Law, Universitas Pekalongan, 2024)
Currently the country is trying to improve Human Resources (HR) on a large scale, especially in Indonesia to advance the nation, but the high rate of early marriage has an impact on the progress of the younger generation where marriages that are held without careful preparation both from the economy, education, psychology and sociology also have an impact on the next generation born and personal and social development in society also occurs unprepared. Law No. 1 of 1974 Jo Law No. 16 of 2019 About was passed by the government as an effort to prevent early marriage by limiting the minimum age of 19 years for men and women. The purpose of this research is to find out what factors cause the application for marriage dispensation and obstacles in the application for marriage dispensation in religious courts and what steps are used in the event of rejection of the application. The method used The data collection method used in this research is an empirical juridical review by conducting observations, comparisons and interviews with sources from the Religious Court and informants who apply for marriage dispensation. Causes for advocating marriage dispensation include religious reasons, special circumstances, parental/guardian consent, legal considerations. In the implementation of the application for marriage dispensation, there are also obstacles, namely the difficulty of completing data. In the event of rejection of the application for marriage dispensation, the applicant can make cassation.